Penegakan Hukum di Indonesia: Sebuah Harapan dan Kenyataan - Rif'ah Roihanah (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2015)
The problem of law enforcement is an interesting thing to discuss, especially because there is an imbalance between the legal aspects of expectations and aspects of legal application in reality. Ironically, public compliance with the law is very concerning. This is triggered by weak law enforcement. It can be said that the law in this country is sharp downwards and blunt upwards. Law enforcement should be accountable (responsible), impartial and not easily intervened so that the results can be accounted for before the public. People need legal certainty over the legal system that applies in this country, because law enforcement cannot stand alone without the legal system itself. To establish and build an accountable law enforcement system, it is necessary to involve all stakeholders and most importantly the support of a clean government. The government must be at the forefront of law enforcement to provide hope to the public for legal certainty.